Photovoice in Laos: Innovative Approach in Communicating Climate Change Challenges and Adaptation Option - Villanueva, Jerome; Joven, Bernadette; Khounthavong, Malisa; Nelakhom, Phalida; Wassmann, Reiner; Chanthakouman, Ketsana; Phommasack, Outhen (2018)
Implementing Photovoice in Lao's Climate-Smart Villages showcase innovative ways in capturing issues brought about by climate change. This particular tool vividly describe impacts that are highly detrimental to the livelihood of farmers and agricultural landscape. The use of photographs taken by farmers in sharing issues and challenges promote elevated interest for a distinct target audience. The magnitude of a particular scenario is then easily understood and can be readily relate upon. Here we expand the importance of Photovoice as an effective communication tool in capturing and sharing climate-related issues and adaptation option that can be use by researchers and development workers to design and implement potential climate-smart agriculture practices incorporating grassroots participatory approach in the project design.